Guide to forensic pathology practice for death cases related to coronavirus disease 2019 (COVID-19) (Trial draft) - Danmi Mao; Nan Zhou; Da Zheng; Jiacheng Yue; Qianhao Zhao; Bin Luo; Dawei Guan; Yiwu Zhou; Bingjie Hu (Oxford University Press, 2020)
Autopsy is of great significance for elucidating the pathological changes, pathogenesis and cause of death of Coronavirus Disease 2019 (COVID-19) and can provide a theoretical basis for scientific and accurate prevention and control of its outbreak. Based on related laws and regulations, such as the Law of the People's Republic of China on Prevention and Control of Infectious Diseases, clinical manifestations and epidemiological characteristics of COVID-19 and guidelines on the prevention and control of this epidemic, combined with the practical work of forensic pathology examinations, we developed the Guide to Forensic Pathology Practice for Death Cases Related to Coronavirus Disease 2019 (COVID-19) (Trial Draft). This guide describes the background investigation of the death cases, autopsy room requirements, personal prevention and protections, external examinations, autopsy practices and auxiliary examinations, and thus offers a reference for forensic and pathological examination institutions and staff.